Eksistensi Cerita Cupak Gerantang Pada Masyarakat Bali dan Lombok - Armini, I Gusti Ayu; Sudarma, I Wayan (Dharma Sastra : Jurnal Penelitian Bahasa dan Sastra Daerah, 2023)
The story of Cupak Gerantang is existence in Bali and Lombok society. This story is a continuation of Old Javanese literature which existed rapidly during the Majapahit Empire. In Bali, this story is written on palm leaves (called ntal) in geguritan form or song story. That’s a continuation of Old Javanese literature which developed rapidly during the glory of the Gelgel Kingdom era. In Lombok, the Cupak Gurantang story is also a continuation of Old Javanese literature, is written in palm leaves too (called takepan) in the Sasak language. The main problem that becomes the topic of discussion include three question. How are existed the Cupak Gerantang story in Bali and Lombok. How are similarties of the Cupak Gerantang story in Bali and Cupak Gurantang story in Lombok. How to use the Cupak Gerantang story for Balinese and Lombok people. Data collection used in-depth interviews, observation, and literature. This method is used to collect qualitative data from primary and secondary data. Based on the results of data collection, the Cupak Gerantang story in Bali and Lombok have similarities. The similarities appear in the origins, storylines, values, and moral messages. The difference lies in the location setting, the names of the supporting characters, and the method of staging. Both, in Bali and Lombok the Cupak Gurantang story used as entertainment, information media, suggestive function, and veiled resistance. In this story contain to as moral values ​​including the value of togetherness, mutual help, and ethics. That are used as a reference for human activity.